"Assisted vaginal birth using the Paily obstetric forceps vs Ventouse – A randomized clinical trial". (January 2023) - Burande, Anuprita Prakash; Jayaraj, Vasanthi; Pai, Anitha V.; Akkarappatty, Philo; Arathi, V.L.; Pradeep, Manu; Paily, Vakkanal Paily
Abstract: Objective: Instruments used in assisted vaginal birth have seen little innovation for decades. Due to the risk of trauma and technical difficulty incurred during forceps delivery, instrumental deliveries are on a decline, and the global rate of primary cesarean birth is rising. The novel Paily Obstetric Forceps (POF) features a compact, lighter design with thinner blades, designed to increase operator comfort and minimize maternal and neonatal injuries. We aim to determine the feasibility and safety of POF in achieving vaginal birth compared to a ventouse device with a 50 mm silastic cup. Study Design: We conducted a single-blinded, parallel arm, randomized clinical trial of the novel POF vs a ventouse device, in patients undergoing indicated assisted vaginal birth, at a tertiary care obstetric unit. We randomized 100 patients to be allocated on a 1:1 ratio to both intervention arms. Primary outcome was the proportion of successful instrumental deliveries. Secondary outcomes were the number of pulls required during traction and any maternal or neonatal adverse events. Results: The POF was significantly more successful in achieving vaginal birth than the ventouse device (n = 50/50, 100 % vs n = 42/50, 84 %, p = 0.006). Operators reported requiring significantly fewer pulls during POF traction than ventouse. POF demonstrated a higher risk for maternal trauma (RR = 3.2, 95 % CI = 1.5 to 6.9, NNH = 2.7) but a lower risk for neonatal injury (RR = 0.6, 95 % CI = 0.3 to 1, NNH = 5.7). Maternal and neonatal recovery durations were comparable. There were no incidences of maternal or neonatal mortality. Conclusion: The POF can be used in indicated assisted vaginal birth with superior success rates and better neonatal outcomes than ventouse. Other obstetric forceps must be standardized to conduct larger superiority trials of forceps designs.